How Broad Is the Understanding of Security in Local Communities: The Views of the Mayors of Some Municipalities in Posavje Region - Sotlar, Andrej; Tominc, Bernarda (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Municipalities have certain legal responsibilities in the field of ensuring security. Since they vary in terms of size, personnel and material capacities, as well as security issues, it is not unimportant how mayors understand and deal with security, security phenomena and problems. We know that what is an official assessment of the state of security and its provision at the national level does not necessarily apply to municipalities or regions. The (statistical) Posavje region certainly belongs among the security-interesting regions. Due to its geographical location, proximity to the border and related issues, critical infrastructure, locally specific security issues, etc., it is heterogeneous in terms of security, but extremely interesting to study. At the same time, it increasingly appears as a well-rounded political and economic entity. Therefore, the paper presents the views of the interviewed mayors of some Posavje municipalities on security and related issues.